Diagnostic Value of Urine Ribonuclease 7 (RNase 7) to Creatinine Ratio for Detecting Urinary Tract Infection in Children with Pyuria - Cetin, Nuran; Kiraz, Zeynep Kusku; Gencler, Aylin (Journal of Pediatric Infectious Diseases, 2022)
Objective Ribonuclease 7 (RNase 7) is one of the members of the antimicrobial peptides playing a role in maintaining urinary tract sterility. We aimed to investigate the predictive value of the urine RNase 7 levels in children with pyuria and associations between RNase 7 and vesicoureteral reflux (VUR) and renal scarring.Methods This study included 109 children with pyuria (46 febrile urinary tract infections [UTIs], 38 nonfebrile UTIs, and 25 sterile pyuria) whose RNase 7 levels were measured by enzyme-linked immunoassay. The results for urine RNase 7 concentrations were expressed as micrograms per milligrams creatinine.Results RNase 7/Cr levels were higher in patients with both febrile and nonfebrile UTIs than the patients with sterile pyuria (p = 0.001). RNase 7/Cr had predictive values of diagnosis of febrile and nonfebrile UTIs (cut-off value: 2.92 µg/mg, p = 0.003; cut-off value: 3.67 µg/mg, p < 0.001, respectively). RNase 7/Cr had higher levels in the patients with VUR than without VUR (cut-off value: 4.28 µg/mg, p = 0.037). The patients with renal scarring had higher urine RNase 7/Cr than those without scarring (cut-off value: 4.54 µg/mg, p = 0.041).Conclusion The evaluation of RNase 7/Cr may help prevent unnecessary and/or inappropriate antibiotic use in children with pyuria. The higher RNase 7 levels in patients with VUR and renal scarring may reflect long-term inflammation or greater inflammatory response during acute infection.
Keywords: children; renal scarring; ribonuclease 7; urinary tract infection; vesicoureteral reflux